2007
DOI: 10.1111/j.1708-8305.2007.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Korean Travelers’ Knowledge, Attitudes, and Practices Regarding the Prevention of Malaria: Measures Taken by Travelers Departing for India From Incheon International Airport

Abstract: There is an urgent need for increased awareness about travel-related infectious diseases (especially malaria) among Korean travelers, and they should be encouraged to seek pretravel health information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
7
18
1
Order By: Relevance
“…Travel medicine providers were particularly underutilized; only 25.5% of the travelers reporting having sought pre-travel consultations in the current survey. This finding is comparable to the rates that have been reported in similar studies [8][9][10][11][12][13][14][15][16][17]25]. Those traveling for leisure and for business were more likely to pursue health information than those traveling to VFRs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Travel medicine providers were particularly underutilized; only 25.5% of the travelers reporting having sought pre-travel consultations in the current survey. This finding is comparable to the rates that have been reported in similar studies [8][9][10][11][12][13][14][15][16][17]25]. Those traveling for leisure and for business were more likely to pursue health information than those traveling to VFRs.…”
Section: Discussionsupporting
confidence: 86%
“…Only 41.2% of Western that are ill following returning from Asian countries reported that they had a pre-travel visit [5]. Few other studies on the pre-travel health-seeking behavior of travelers to the Asia-Pacific region suggest that the proportion of Asian travelers who attend pre-travel consultations is even lower than that of Western travelers [14][15][16][17].…”
Section: Introductionmentioning
confidence: 98%
“…This can be explained by hidden fears and the inability to cope with stress and risks. 27 Education provides better opportunities and skills to deal with risks, and that might decrease one's perception of endangering risks. However, gender, age, destination, and region-related travel experience had different impacts on the travelers' risk perception.…”
Section: Unlike Most European Travelers Among Whom Travelers Tomentioning
confidence: 99%
“…There were 15 studies conducted in travelers recruited at airports [8,15e17,20,22,31e33,35e39,43,44] and one onboard flight [41], in Europe [8,15e17,32,37,39], Asia [20,33,36], Australia [36], US [22,38] and Canada [41] before flying abroad or at airports in Africa [31,35,43,44] and Asia [31] before flying back home. Thirteen studies included travelers recruited at travel clinics when seeking travel advice [7,9e12,14,23,24,28,29,34,40,42] in Europe [7,11,12,14,23,24,28,34,40], Australia [9], US [10], Canada [42] and Asia [29].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Some studies combined several sources of recruitment [7,29,34]. A total of 14 studies focused on a group of selected infectious diseases, including notably malaria, hepatitis A and B and HIV infection [12,13,19,25,27,30,32,35e39,41,42]; 13 focused on malaria only [10,15,16,18,20,21,26,29,31,33,34,40,43,44], 2 on respiratory tract infections [9,24], 2 on influenza [22,23], 2 on rabies [28,45], and 1 each on Ebola [6], pneumococcal disease [7], hepatitis A [17], hepatitis B [8], infections transmitted through camel milk consumption [11] and Middle East respiratory syndrome [14]. Key findings are reported in Table 1 and show an overall underestimation of risks.…”
Section: Study Characteristicsmentioning
confidence: 99%